Distribution System Analysis of PT AGRICON in Oil Palm Plantation Sector - Wijaya, Ryan Gulfa; Wandebori, Harimukti (Journal of Business and Management, 2012)
Indonesia is an agrarian nation, which means that agriculture is the main activity and job for the citizen in this nation, this fact making pesticide a common product to be used by the farmers. Agricon has been largely known as a producer of high quality pesticide products for food and horticulture crops, while the plantation market side has not been seriously handled. Currently Agricon is aiming new sector of market, palm oil plantations. In the past, mainly independent distributors handled the marketing and distribution of Agricon’s pesticide products in the plantation sector market. Agricon now wants to directly deal with plantation companies. This report will discuss about the distribution system of Agricon’s pesticide products in the plantation sector, analyzing its current system and finally making a conclusion about which is the best distribution system regarding the marketing in the oil palm plantation sector.By using direct selling and channeling strategy theory in conducting in depth interview to analyze the system. Therefore, PT. Agricon is suitable and should conduct direct selling and distribution to the big buyer but still utilize distributor as assistant and using distributor and wholesaler for medium and small buyer.Purpose:To Analyze PT. Agricon current distribution system and improving it by making the suitable distribution system.Design/methodology/approach:By analyzing current condition and distribution system of PT. Agricon as base of the research then analyzing the system suitability by using direct selling by manufacturing and channeling strategy theory. Conducting in depth interview to PT. Agricon executives as primary data and distributor and competitor as supporting data as comparison.Findings:The researcher discover that PT. Agricon is still in the state of preparing the employees; direct selling should be conducted to big buyer to avoid price war, PT. Agricon should still use distributor for assistance and in dealing with medium and small buyer because distributor can be a competitor also so they still must be used. PT. Agricon should improve their method in the agreement with distributor.Research limitations/implications:The research only to choose the best distribution system of PT. Agricon and only in the oil palm plantation sector.Practical implications:The outcome and output of this research is the suitable and probably the best distribution system of PT. Agricon in oil palm plantation sector.Originality/value:The analysis about oil palm plantation market condition and the best distribution system for local pesticide industry.Keywords-component; Pesticide, Oil Palm Plantation,CategoryDistribution Channel; Marketing